Trigger finger: comparative study between corticosteroid injection and percutaneous release - Singh, V.A.; Chong, S.; Marriapan, S. (2006)
Background: Trigger finger (stenosing tenosynovitis) is a common problem encountered in orthopaedic practice. There are various methods of treatment ranging from conservative management to surgical release. Aim: To determine effectiveness of corticosteroid injection and percutaneous release; in terms of symptomatic relieve, patient satisfaction and complications. Material & Methods: Prospective study. All patients who presented with trigger finger Grade 2 and 3 were randomized into 2 groups. One group received corticosteroid injection and in the other group, percutaneous release was done. These patients were then assessed weekly over a period of one month and their progress noted. Results: We studied a total of 26 patients. Majority (65.4) were females. The commonest age group is 50-60 years olds (45.6). Thirty eight and a half percent were manual workers, 30.8 semi-professionals followed by 26.9 housewives. There was almost equal involvement of dominant (53.8) and non-dominant hand (46.2). The most common presenting symptom was pain with triggering (42.3). The middle and ring were most commonly affected (42.2 each). The little finger was not involved at all. There was significant improvement in pain in the first two weeks in both groups but there was better improvement of pain in the corticosteroid group especially on the 1st and the 4th week. As for the triggering, there was significant improvement noted in 1st week but there was no difference in degree of improvement between both the groups. There was no significant difference was noted in the progress of swelling during the course of the treatment in either group. As for patient satisfaction, the percutaneous release group reached maximum satisfaction by 2 weeks as oppose to the corticosteroid group, which achieve maximum satisfaction 1 week later. The corticosteroid group had a complication rate of 10 whereas the percutaneous release group complication rate was 20. The recurrence rate was 15. There were 2 cases in each group. Occurring 2 to 9 months after the primary procedure. Conclusion: Trigger finger is a common condition amongst blue-collar workers. The commonly affected fingers are the centrally located on the palm. The group of patients treated with corticosteroid had better relieve of pain but took longer to achieve maximum satisfaction as compared to the group that underwent percutaneous release. Both method of treatment eventually gave similar results after 3 weeks but the percutaneous release group had a higher complication rate. Recurrence was equal in both groups.